2019
DOI: 10.5296/jas.v7i3.15313
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Neem, Tithonia and Tephrosia Leaf Extracts in Management of Root-Knot Nematodes in French Beans (Phaseolus vulgaris L.)

Abstract: Root-knot nematodes (Meloidogyne spp.) are a major problem in French bean production within the smallholder farming systems. Control of root-knot using synthetic nematicides is not viable due to environmental concerns relating to their toxic residues. There is need to develop alternative control options that will promote soil health and reduce parasitic nematode densities. A study was conducted to determine the efficacy of Neem (Azadirachta indica A. Juss), Tithonia (Tithonia diversifolia) and Tephrosia (Tephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The results from the molluscicidal activities showed that the extracts of commercial wastes (groundnut shells, garlic skin and coffee grounds) and bioresource (water spinach) extracts were lethal on GAS (Njenga, 2019) showing different time frame of cidal effects on apple snail. The strongest cidal effect as biocontrol nanomaterial was shown by the water spinach aqueous extract (Table 3) and the weakest cidal activity was exhibited by the coffee aqueous extract (Table 2) even though it had the smallest nanoparticle size (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The results from the molluscicidal activities showed that the extracts of commercial wastes (groundnut shells, garlic skin and coffee grounds) and bioresource (water spinach) extracts were lethal on GAS (Njenga, 2019) showing different time frame of cidal effects on apple snail. The strongest cidal effect as biocontrol nanomaterial was shown by the water spinach aqueous extract (Table 3) and the weakest cidal activity was exhibited by the coffee aqueous extract (Table 2) even though it had the smallest nanoparticle size (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The bark powder from Saraca asoca and Acacia nilotica was shown to suppress M. incognita and Rotylenchulus reniformis reproduction, and subsequently improve castor seedling growth when amended in soil at a rate of 50 g/ kg soil (Parveen and Bhat, 2011). In field trials, crude extracts of Tephrosia purpurea were shown to significantly reduce root-galling in French bean (Njenga et al, 2019); while extracts from T. cinerea stem were bioactive against M. incognita (Cristóbal- Alejo et al, 2006). Additionally, extracts of roots and leaves of Leucaena leucocephala have been reported to contain flavonoids like quercetin known to be highly toxic to M. incognita (Adekunle and Aderogba, 2008); Medicago sativa is also known to contain saponin mixture, with nematicidal potency reported against X. index, M. incognita, and G. rostochiensis; and when amended in soil, significant population reductions were evident (D'Addabbo et al, 2011).…”
Section: Composition Activity and Potency Of The Active Constituentsmentioning
confidence: 99%